New learning method with ERP business simulation game: What can we learn? - Octavio, Muhammad Fadhly Rizky; Falikhatun (Master in Accounting Program, Faculty of Business & Economics, Universitas Islam Indonesia, Yogyakarta, Indonesia, 2024)
This Study explores the effectiveness of Enterprise Resource Planning (ERP) business simulation games on user competencies. This Study Uses a qualitative descriptive methodology, and the informants of this research have been winning in national and international business simulation games (both students and alums). Traditional pedagogical approaches need to be revised to explain the rich dynamics arising from business environments. As a result, they also consider incorporating new educational aids into their curriculums, i.e., business simulation games. Participants indicated that interacting with these simulations enhanced their understanding of business topics and resulted in soft skills growth. Current working alumni said they felt more capable of acclimating to the professional world. However, the Study unearthed that comparatively few higher education institutions incorporate business simulation games in their teaching practices. The result shows that with the development of technology, there is a transformation in how business functions; integration of these tools into educational frameworks becomes essential to narrow the knowledge theory gap and knowledge application. These results suggest the importance of universities introducing technology tools, particularly ERP business simulations, into their curricula for Business and Economics courses (single or joint honors) alongside accounting.